Species of Bicellaria Macquart (Diptera: Hybotidae) of Europe, with descriptions of four new species - Barták, Miroslav; Kubík, Štěpán (Zootaxa, 2013)
Species of the genus Bicellaria (Diptera: Hybotidae) of Europe are reviewed. Altogether four new species are described, viz B. andorra sp. nov. (Andorra, France), B. italica sp. nov. (Europe), B. kocoureki sp. nov. (Bulgaria), and B. setipalpus sp. nov. (Italy). Bicellaria dispar Oldenberg, 1920 is redescribed and lectotype is designated. Bicellaria bisetosa Tuomikoski, 1936 is newly synonymized with B. uvens Melander, 1928. Illustrations of male terminalia and a key to all known European species are provided.